The Role of Intraoperative Indocyanine Green (ICG) and Preoperative 3-Dimensional (3D) Reconstruction in Laparoscopic Adrenalectomy: A Propensity Score-matched Analysis. Issue 6 (3rd December 2022) - Palomba, Giuseppe; Dinuzzi, Vincenza Paola; Pegoraro, Francesca; Troisi, Roberto Ivan; Montalti, Roberto; De Palma, Giovanni Domenico; Aprea, Giovanni
Abstract : Background: Laparoscopic adrenalectomy (LA) is considered the "gold standard" treatment of adrenal lesions that are often coincidentally diagnosed during the radiologic workup of other diseases. This study aims to evaluate the intraoperative role of indocyanine green (ICG) fluorescence associated with preoperative 3-dimensional reconstruction (3DR) in laparoscopic adrenalectomy in terms of perioperative outcomes. To our knowledge, this is the first prospective case-controlled report comparing these techniques. Materials and Methods: All consecutive patients aged≥18 and undergoing laparoscopic transperitoneal adrenalectomy for all adrenal masses from January 1, 2019 to January 31, 2022 were prospectively enrolled. Patients undertaking standard LA and those undergoing preoperative 3D reconstruction and intraoperative ICG fluorescence were matched through a one-on-one propensity score matching analysis (PSM) for age, gender, BMI, CCI score, ASA score, lesion histology, tumor side, and lesion diameter. Differences in operative time, blood loss, intraoperative and postoperative complications, conversion rate, and length of stay were analyzed. Results: After propensity score matching analysis, we obtained a cohort of 36 patients divided into 2 groups of 18 patients each. The operative time and intraoperative blood loss were shorter in patients of the 3DR group ( P =0, 004 and P =0, 004, respectively). There was no difference in terms of length of stay, conversion rate, and intraoperative and postoperative complications between the 2 groups. Conclusions: The use of intraoperative ICG in LA and preoperative planning with 3DR images is a safe and useful addition to surgery. Furthermore, we observed a reduction in terms of operating time and intraoperative blood loss.